Understanding Non-Muslims' Purchase Intention: Examining the Effects of Halal Awareness, Certification, and Marketing Factors - Benediktus Rolando (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This research examines the determinants of halal purchase intention among non-Muslim consumers in Indonesia. Utilizing the Theory of Planned Behaviour (TPB) as a conceptual foundation, the study evaluates the influence of halal awareness, certification standards, product attributes, promotional strategies, and brand recognition on consumer intention. Data obtained from 134 non-Muslim respondents across five major Indonesian cities were analysed using structural equation modelling (SEM). Results reveal that all five factors positively influence purchase intention, with brand recognition and certification standards demonstrating the strongest effects, followed by promotional strategies, halal awareness, and product attributes. The model explains 58.3% of the variance in purchase intention, providing robust explanatory power. Significant differences were observed across ethnic groups, with Javanese Christians showing greater acceptance of halal products compared to Chinese Indonesians, highlighting the role of cultural proximity to Islamic traditions. These findings challenge conventional marketing approaches by revealing that non-Muslim consumers rely more heavily on external trust signals (brands and certification) than intrinsic product attributes when considering halal products. Penelitian ini menganalisis faktor-faktor yang mempengaruhi niat pembelian produk halal di kalangan konsumen non-Muslim di Indonesia. Dengan menggunakan Teori Perilaku yang Direncanakan (TPB) sebagai landasan konseptual, studi ini mengevaluasi pengaruh kesadaran halal, standar sertifikasi, atribut produk, strategi promosi, dan pengenalan merek terhadap niat pembelian konsumen. Data yang diperoleh dari 134 responden non-Muslim di lima kota besar di Indonesia dianalisis menggunakan model persamaan struktural (SEM). Hasil menunjukkan bahwa kelima faktor tersebut secara positif mempengaruhi niat pembelian, dengan pengenalan merek dan standar sertifikasi menunjukkan efek terkuat, diikuti oleh strategi promosi, kesadaran halal, dan atribut produk. Model ini menjelaskan 58,3% varians dalam niat pembelian, menunjukkan daya penjelas yang kuat. Perbedaan signifikan diamati antar kelompok etnis, dengan Kristen Jawa menunjukkan penerimaan yang lebih tinggi terhadap produk halal dibandingkan dengan Tionghoa Indonesia, menyoroti peran kedekatan budaya dengan tradisi Islam. Temuan ini menantang pendekatan pemasaran konvensional dengan menunjukkan bahwa konsumen non-Muslim lebih bergantung pada sinyal kepercayaan eksternal (merek dan sertifikasi) daripada atribut produk intrinsik saat mempertimbangkan produk halal.